2020
DOI: 10.1182/bloodadvances.2020001557
|View full text |Cite|
|
Sign up to set email alerts
|

Systematic review of observational studies reporting antiphospholipid antibodies in patients with solid tumors

Abstract: This review summarizes the evidence on antiphospholipid (aPL) antibodies and related thromboembolic events in patients with solid tumors. Data sources included Medline, EMBASE, Web of Science, PubMed ePubs, and the Cochrane Central Register of Controlled Trials through August 2019 without restrictions. Observational studies that evaluated patients with solid tumors for the presence of aPL antibodies were included. Data were extracted and quality was assessed by one reviewer and cross-checked by another. Thirty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 76 publications
(142 reference statements)
1
21
0
2
Order By: Relevance
“…While aPL is present in 1%–5% of the general population, APS prevalence is 40–50/100,000 subjects ( Leal Rato et al., 2021 ). However, this prevalence can increase to 50% among elderly patients with chronic diseases ( Abdel-Wahab et al., 2020 ; Leal Rato et al., 2021 ). Several works report higher aPL levels in various hematological and solid tumors ( Gómez-Puerta et al., 2006 ; Islam, 2020 ), with the percentage of aPL-positive cancer patients varying from 5% to 70%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While aPL is present in 1%–5% of the general population, APS prevalence is 40–50/100,000 subjects ( Leal Rato et al., 2021 ). However, this prevalence can increase to 50% among elderly patients with chronic diseases ( Abdel-Wahab et al., 2020 ; Leal Rato et al., 2021 ). Several works report higher aPL levels in various hematological and solid tumors ( Gómez-Puerta et al., 2006 ; Islam, 2020 ), with the percentage of aPL-positive cancer patients varying from 5% to 70%.…”
Section: Discussionmentioning
confidence: 99%
“…Quantification of results is important, since there is a correlation between the rate of aCL (in particular IgG) and the risk of thrombosis. In view of this, low to moderate aCL levels are taken into consideration in contexts of repeated spontaneous miscarriages ( Abdel-Wahab et al., 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…aPL have also been associated with malignancy. A recent systemic review of observational studies reporting aPL frequency among patients with various solid tumors found that patients with gastrointestinal and lung cancers had 5 times the risk to develop aCL compared to healthy controls while those with genitourinary cancers had 7 times the risk [ 30 ]. Regarding hematologic malignancies, Pusterla et al reported among 100 patients with lymphoma, 24% were positive for aCL while 7% of them were positive for LAC [ 31 ].…”
Section: Frequency Of Antiphospholipid Antibodies In the General Populationmentioning
confidence: 99%
“…Many of them are due to onco-neural auto-antibodies [ 137 ], whose molecular and pathogenic relationship with the original cancer is often difficult to identify. Anti-Ri antibodies [ 138 ], breast cancer anti-phospholipids antibodies [ 139 , 140 ], cerebellar degeneration [ 141 , 142 ], glomerular diseases [ 143 ], and lung cancer [ 144 ] are all conditions which still require a proper pathogenic explanation.…”
Section: Cancer Auto-antibodiesmentioning
confidence: 99%